2013
DOI: 10.1002/jeab.13
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Response‐reinforcer Relations in Periodic and Aperiodic Schedules

Abstract: Key pecking of 4 pigeons was studied under a two-component multiple schedule in which food deliveries were arranged according to a fixed and a variable interfood interval. The percentage of response-dependent food in each component was varied, first in ascending (0, 10, 30, 70 and 100%) and then in descending orders, in successive conditions. The change in response rates was positively related to the percentage of response-dependent food in each schedule component. Across conditions, positively accelerated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
18
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 28 publications
8
18
0
5
Order By: Relevance
“…Several empirical studies discredit adventitious reinforcement. Rachlin and Baum () found that when contingent and noncontingent food are mixed, pigeons' responding discriminates between the two sources of food in the same way as if they were both contingent from two different keys (see also Kuroda et al, ). Killeen () found that pigeons in a detection task accurately distinguished contingent from noncontingent food.…”
Section: Discussionmentioning
confidence: 99%
“…Several empirical studies discredit adventitious reinforcement. Rachlin and Baum () found that when contingent and noncontingent food are mixed, pigeons' responding discriminates between the two sources of food in the same way as if they were both contingent from two different keys (see also Kuroda et al, ). Killeen () found that pigeons in a detection task accurately distinguished contingent from noncontingent food.…”
Section: Discussionmentioning
confidence: 99%
“…In application, NCR is often used as a control in functional analyses of problem behavior (control or toy play condition; see Beavers, Iwata, &Lerman, 2013, andMcCord, 2003) and as a treatment for problem behavior (e.g., Vollmer et al). Its use as a behavioral treatment stems from basic research demonstrating response-independent presentations of reinforcing events (e.g., food) decrease rates of a target response (e.g., Kuroda et al, 2013;Podlesnik & Shahan, 2008).…”
mentioning
confidence: 99%
“…In the right graphs of this figure, the data from the left graphs are displayed as means across conditions in which the dependency in the alternative component was 10, 50, and 100%. Across conditions, reinforcement rates were similar between components for each rat, and Baseline response rates were directly related to the dependency in each component (Kuroda et al, ; Lattal, ). That is, in conditions in which the dependency in the alternative component was 100%, response rates in both components were similar.…”
Section: Resultsmentioning
confidence: 99%
“…The 10% components differed on how reinforcers were programmed. In one component, responsedependent and -independent reinforcers were programmed as in Experiment 1 (Kuroda et al, 2013;Lattal, 1974); in the other component, those reinforcers were programmed by superimposing a VT schedule on an independent VI schedule (Nevin et al, 1990;Podlesnik & Shahan, 2008).…”
Section: Methodsmentioning
confidence: 99%